Iodine‐Chemisorption, Interpenetration and Polycatenation: Cationic MOFs and CPs from Group 13 Metal Halides and Di‐Pyridyl‐Linkers - Schäfer, Thomas C.; Becker, Jonathan; Seuffert, Marcel T.; Heuler, Dominik; Sedykh, Alexander E.; Müller‐Buschbaum, Klaus (Chemistry : a European journal, 2022)
Eight cationic, two‐dimensional metal‐organic frameworks (MOFs) were synthesized in reactions of the group 13 metal halides AlBr3, AlI3, GaBr3, InBr3 and InI3 with the dipyridyl ligands 1,2‐di(4‐pyridyl)ethylene (bpe), 1,2‐di(4‐pyridyl)ethane (bpa) and 4,4’‐bipyridine (bipy). Seven of them follow the general formula 2∞[MX2(L)2]A, M=Al, In, X=Br, I, A−=[MX4]−, I−, I3−, L=bipy, bpa, bpe. Thereby, the porosity of the cationic frameworks can be utilized to take up the heavy molecule iodine in gas‐phase chemisorption vital for the capture of iodine radioisotopes. This is achieved by switching between I− and the polyiodide I3− in the cavities at room temperature, including single‐crystal‐to‐single‐crystal transformation. The MOFs are 2D networks that exhibit (4,4)‐topology in general or (6,3)‐topology for 2∞[(GaBr2)2(bpa)5][GaBr4]2⋅bpa. The two‐dimensional networks can either be arranged to an inclined interpenetration of the cationic two‐dimensional networks, or to stacked networks without interpenetration. Interpenetration is accompanied by polycatenation. Due to the cationic character, the MOFs require the counter ions [MX4]−, I− or I3− counter ions in their pores. Whereas the [MX4]−, ions are immobile, iodide allows for chemisorption. Furthermore, eight additional coordination polymers and complexes were identified and isolated that elaborate the reaction space of the herein reported syntheses. Reactions of iodides and bromides of Al, Ga and In with dipyridyl ligands under various conditions lead to a large number of products including cationic two‐dimensional MOFs that exhibit interpenetration and polycatenation. Charge compensation is achieved via tetra‐halido‐metal anions and iodide anions. The latter allows for chemisorption of I2 under formation of I3− suitable for the capture of radioisotopes of iodine.